2023
DOI: 10.3390/su16010116
|View full text |Cite
|
Sign up to set email alerts
|

Flood Inundation and Streamflow Changes in the Kabul River Basin under Climate Change

Sohaib Baig,
Shabeh ul Hasson

Abstract: The Kabul basin yields around 16% of the total annual water availability in Pakistan. Changing climate will alter the precipitation regime in terms of intensity and frequency, which will affect the water yield and cause flood hazards. Against this background, this study aims to quantify the impacts of changing climate on the water yield, its timings, and, more importantly, the associated flood hazards in the transboundary Kabul basin. For this, we used a rainfall-runoff inundation (RRI) model coupled with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, compared to the baseline period, there will be an increase in the seasonal streamflow during the rainy season and decreases in the dry season. The studies [42,51,52] also suggest that summer flows will continue to drop in the future, whereas spring and winter flows will increase in the Indus River Basin. The seasonal variation in streamflow can lead to more frequent floods during the wet season and droughts during the dry season due to less runoff and a higher ET in the UKRB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, compared to the baseline period, there will be an increase in the seasonal streamflow during the rainy season and decreases in the dry season. The studies [42,51,52] also suggest that summer flows will continue to drop in the future, whereas spring and winter flows will increase in the Indus River Basin. The seasonal variation in streamflow can lead to more frequent floods during the wet season and droughts during the dry season due to less runoff and a higher ET in the UKRB.…”
Section: Discussionmentioning
confidence: 97%
“…It is quite clear that the water regime of the Indus River will have a decisive influence on the tributaries, including the Kabul River, in the future. Sohaib et al [42] found future seasonal shifts in the streamflow and the rainfall shifts at the Nowshera and Chitral watershed of KRB, and Ref. [18] found that the peak hydrograph split into two peaks; one formed in Mar-Apr indicated earlier snowmelt, and the second one in August, which was due to Monsoon rains increased in the Alingar watershed of the KRB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation